2020
DOI: 10.1186/s12906-020-02891-x
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic approach to HPLC analysis, antinociceptive, anti-inflammatory and postoperative analgesic activities of panch phoron in mice

Abstract: Background: Panch phoron is a mixture of five spices containing an equal proportion of Foeniculum vulgare (fennel), Trigonella foenum-graecum Linn (fenugreek), Nigella sativa (black cumin), Cuminum cyminum (cumin) and Brassica nigra (black mustard). The mixture is commonly used in Bangladeshi cuisine and possesses many pharmacological effects. In this study, we evaluated the antinociceptive and anti-inflammatory activities of aqueous panch phoron extract (PPE) in vivo, its possible mechanism of action and phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…Although there are plenty of data on its antioxidant, antidepressant, neuroprotectant, and anxiolytic effects, yet its role in improving functional recovery following PNI has never been dissected. Recent studies have reported the potential neuroprotective effects (Gias et al., 2020) and neuroregenerative effects depicting functional recovery (Imran et al., 2019) following sciatic nerve crush injury in a mouse model of fennel seeds. So, here we investigate the possible effect of F. vulgare methanolic extract on escalating functional recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are plenty of data on its antioxidant, antidepressant, neuroprotectant, and anxiolytic effects, yet its role in improving functional recovery following PNI has never been dissected. Recent studies have reported the potential neuroprotective effects (Gias et al., 2020) and neuroregenerative effects depicting functional recovery (Imran et al., 2019) following sciatic nerve crush injury in a mouse model of fennel seeds. So, here we investigate the possible effect of F. vulgare methanolic extract on escalating functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Having antioxidant, analgesic, and anti‐inflammatory properties, it can be assumed that fennel can be a good candidate to be considered as an alternative therapeutic agent in escalating functional recovery following nerve injuries. Recently, panch phoron, which is a blend of five spices including Foeniculum vulgare, has shown antinociceptive and anti‐inflammatory activities in sciatic nerve crush injury mice model (Gias et al., 2020). Our group has recently demonstrated the positive impact of crude fennel seed supplementation in a mouse model of PNI (Imran et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is an essential defense and survivorship mechanism against harmful stimuli and bodily injuries [1,2]. The inflammatory process involves complex responses from a variety of mediators capable of eliciting heat, flushing, edema, pain, or loss of function of the inflamed tissues [3–5].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic limitation of the available glucocorticoids, nonsteroidal anti‐inflammatory drugs (NSAIDs), and opioids has increased the interest in pyrazole derivatives [2,9,10]. The pyrazole ring ( Figure ) characterizes pyrazole derivatives, such as the celecoxib ( 5 ), fomepizole ( 7 ), among others ( Figure ) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Syringic acid has been generally used in clinical practice and the industrial sector [15]. According to the published reports, syringic acid has been demonstrated to reduce pain in acute pancreatitis and several plant extracts with syringic acid have been found to be effective in alleviating pain [18][19][20].…”
mentioning
confidence: 99%